2020
DOI: 10.3389/fmicb.2020.00493
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella-Like Endosymbiont of Rhipicephalus sanguineus Is Required for Physiological Processes During Ontogeny

Abstract: Obligatory hematophagous arthropods such as lice, bugs, flies, and ticks harbor bacterial endosymbionts that are expected to complement missing essential nutrients in their diet. Genomic and some experimental evidence support this expectation. Hard ticks (Acari: Ixodidae) are associated with several lineages of bacterial symbionts, and very few were experimentally shown to be essential to some aspects of tick's fitness. In order to pinpoint the nature of interactions between hard ticks and their symbionts, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 44 publications
(67 reference statements)
2
72
0
Order By: Relevance
“…Despite these apparently contradictory experimental results, primary symbionts from other hematophagous arthropods do provide B vitamins to their host. The development and reproduction of ticks, lice, Tse-Tse flies, and bedbugs all rely on primary endosymbionts in bacteriomes or mycetomes that supply B vitamins and other nutrients [ 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ]. Furthermore, all these primary symbionts have enzymes and genes involved in the de novo synthesis of B vitamins, as does R. rhodnii [ 206 , 214 , 215 ].…”
Section: Triatomine Symbiosesmentioning
confidence: 99%
“…Despite these apparently contradictory experimental results, primary symbionts from other hematophagous arthropods do provide B vitamins to their host. The development and reproduction of ticks, lice, Tse-Tse flies, and bedbugs all rely on primary endosymbionts in bacteriomes or mycetomes that supply B vitamins and other nutrients [ 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ]. Furthermore, all these primary symbionts have enzymes and genes involved in the de novo synthesis of B vitamins, as does R. rhodnii [ 206 , 214 , 215 ].…”
Section: Triatomine Symbiosesmentioning
confidence: 99%
“…characterized, previous studies have shown that they are often the sole bacterium present in longterm laboratory tick colonies, an indication that the bacteria are essential to ticks' wellbeing. In addition, removal of the resident endosymbiont via antibiotic treatment reduced tick fitness, which was reversed when ticks were provided with B vitamins (Zhong et al 2007;Smith et al 2015;Gerhart et al 2016;Guizzo et al 2017;Zhang et al 2017;Duron et al 2018b;Li et al 2018;Ben-Yosef et al 2020). Our genome analyses support a B vitamin-provisioning role for tick endosymbionts because the genes required to synthesize B7 (biotin), B9 (folic acid), and B2 (riboflavin), and three coenzymes (FAD, CoA, and lipoic acid) are conserved in all CLEs and FLEs.…”
Section: Functions Of Cles and Fles While The Exact Functions Of Flementioning
confidence: 70%
“…Our results are similar to studies on I. ricinus and I. paci cus that found that injection of antibiotics into engorged females had no effect on their reproductive tness 38,39 . In other tick species that carry nutritional symbionts, such as Coxiella-like endosymbionts and Francisella-like endosymbionts that provide B vitamins, antibiotic treatments reduced tick tness (e.g., moulting rate, body weight, fecundity, larval survival) and induced physical abnormalities [15][16][17][18][19][20] . Normal tick phenotypes were recovered after combining the antibiotic treatment with an arti cial blood meal that contained the missing B vitamins 19,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Some are obligate symbionts that provide a critical function, for example providing a vitamin that is missing from a nutrient-poor hematophagous (blood-based) diet 14 . The general importance of arthropod-symbiont associations can be demonstrated by dysbiosis treatments (e.g., antibiotics) that decrease the abundance of the symbiont resulting in dramatic reductions in the tness of the arthropod vector [15][16][17][18][19][20] . These non-pathogenic bacteria can also in uence vector competence, which is the ability of the arthropod vector to acquire, maintain, and transmit vector-borne pathogens over its lifecycle [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%